Goodwill and Evaluation of Organization’s Effectiveness - I. D. Demina; D. A. Bezrukov (Учёт. Анализ. Аудит)
The article describes the relationship between value creation, performance measurement and accounting for goodwill in accordance with the IFRS and US-GAAP. It shows how to use accounting information collected to verify goodwill for impairment in accordance with IAS36 (“Impairment of Assets”), and FAS142 (“Goodwill and Other Intangible Assets”) to improve internal control. The authors prove that the information for estimating goodwill of a company can make the foundation for the development of a system of performance measurement, which in turn provides the data about value creation and its future use. The paper provides practical evidence that adjustments of the information used for impairment testing generate the data which meet the requirements of optimal system of performance management. The paper contributes to the theory of accounting by developing an innovative indicator to measure the performance of the actual value created.